Analysis Of Student Performance Using Massive Open Online Courses As Blended Learning Approach In Learning Second Language - Hashim, Hasmaini (Centre For Advanced Research On Energy (CARe) UTeM, 2017)
Massive Open Online Course (MOOC) provides an effective learning platform with various high-quality educational materials accessible to learners from all over the world. However, there are still problems and challenges including assessment and lack of engagement. This paper analyses students’ performance in using MOOC as a blended learning approach to learn a Second Language.